Venous ulcer: clinical characteristics and risk factors - Abbade, Luciana Patrícia Fernandes [UNESP]; Lastoria, Sidnei [UNESP]; Rollo, Hamilton Almeida [UNESP] (Wiley-Blackwell, 2011)
BackgroundLower limb venous ulceration ranks among the 10 most common medical problems in Western countries and has significant socioeconomic impact. The aim of this study was to identify the risk factors for unhealed, recurrent, and large ulcers and to characterize patients with active or recently healed venous ulcers.MethodsWe identified 97 patients and assessed 103 ulcerated limbs in 90 patients. All patients underwent clinical examination, arterial and venous system evaluation, ankle-brachial index determination, and ultrasound of the affected limb. Clinical characteristics included age, gender, race, ulcer duration, time since first episode, history of recurrence, localization of ulcer, ulcer area, eczema, ochre dermatitis, lipodermatosclerosis, pain, body mass index, and medical history data. Risk factors were identified by univariate analysis and estimated odds ratios.ResultsWe assessed 90 patients (103 limbs) with active or healed venous leg ulcers, of whom 84.4% were Caucasian and 68.9% were female. Mean age was 56.0 +/- 13.3 years. Ulcers had remained unhealed for < 1 year in 40.7%. Lipodermatosclerosis, lower limb hyperpigmentation, edema, and eczema were seen in 96.7%, 95.6%, 94.4%, and 51.1% of patients, respectively. Pain was a frequent symptom in 74.4%. Body mass index was assessed in 85 patients: 30.6% were slightly, 36.5% moderately, and 7% severely obese. Patient age > 60 years (odds ratio [OR] 4.0), extensive lipodermatosclerosis (OR 8.7), and previous history of ulceration (OR 19.9) were risk factors for unhealed ulcers. Time since first ulcer episode >= 2 years (OR 29.2) and incompetence of venous systems (OR 1.6) were risk factors for recurrence.ConclusionsLongstanding and large ulcers and recurrences are the main problems encountered by venous ulcer patients. Severe lipodermatosclerosis, previous ulcer history, and time since first ulcer episode >= 2 years are significant risk factors.